Perancangan Website Promosi Pada PT. Mitra Kerinci Padang - Rofil M. Nur (fakultas Desain Koomunikasi visual, 2021)
PT. Mitra Kerinci is a tea plantation company that has an office in Padang. Website promotion, especially at PT. Mitra Kerinci Padang does not yet have a website capable of providing information. On the basis of the problems that occur, the author has conducted research to design a promotional information system for PT. Partners of Kerinci Padang. In the process, the output design, input design and file design are designed, which are then implemented into the PHP programming language supported by the MySQL database. With the existence of a promotional website at PT. This Padang Kerinci partner, can provide information that is effective and easily accessible to users.